Can social assistance reduce violent conflict and civil unrest? Evidence from a large-scale public works programme in Ethiopia - Hirvonen, Kalle; Machado, Elia; Simons, Andrew M. (United Nations University, 2024)
We assess how one of the largest public works programmes in the world—Ethiopia’s Productive Safety Net Programme (PSNP)—affected violent conflict and civil unrest. Using difference-in-differences methods and linking administrative and geocoded conflict event data, we find that the PSNP did not change the risk of violent events, but reduced the likelihood of civil unrest by almost half when compared to non-PSNP districts. These effects are most pronounced during the period 2014–18, coinciding with widespread protests in Amhara and Oromia, the two most populous regions of Ethiopia. Examining mechanisms, we find evidence that the PSNP fostered greater sympathy and satisfaction with the ruling party, making PSNP households less likely to engage in demonstrations.